Non‐random patterns of functional redundancy revealed in ground beetle communities facing an extreme flood event. (24th March 2014) - Gerisch, Michael; Harwood, James
Summary Theory predicts that species performing similar roles for ecological processes or functions can compensate for the loss of others and that this functional redundancy may promote resilience. However, there is no clear evidence for this mechanism, because functional redundancy has been observed to be low in many ecosystems. Using a severe flood event, this study tests whether functional redundancy exists in floodplain ground beetle communities, how it is controlled and how it connects to post‐flood resilience. Ground beetles were sampled in floodplain grassland of the Elbe River, Germany. Functional redundancy was estimated as the proportion of species in a community having neutral effects on functional diversity. Null models were used to determine whether functional redundancy is higher or lower than expected and mixed effects modelling was applied to estimate the relationships between functional redundancy, flood disturbance and sampling season. It was found that highly redundant ground beetle communities experienced fewer losses in functional diversity caused by an extreme flood than less redundant communities. Functional redundancy was lowest immediately after the flood, but quickly increased with time since flooding. It was significantly higher in spring than in autumn seasons and significantly higher in habitats exposed to frequent flooding. Null models confirmed that these patterns were to a high degree non‐random. The results indicate that functional redundancy plays an important role for stabilizing ground beetles under regular, predictable flooding. However, given sizeable differences in functional diversity before and after the extreme flood, this effect may be lower than expected during extreme events. Other regulating forces, such as stochastic colonization processes and habitat templets, play more important roles directly after extreme disturbances. I therefore assume that a temporal hierarchy of mechanisms, including FR, controls the functional diversity of ground beetles in riparian habitats.